Reseña: Juan Vespucci (1487–ca. 1527) - Manuel Morato-Morano (Boletín de la Asociación de Geógrafos Españoles)
Robles Macías, Luis A. Juan Vespucci (1487–ca. 1527): A Cosmographer, Seaman and Merchant at the Heart of Spanish Charting of the New World. Universidad Libre de Bruselas (Bélgica), enero 2024. Director: Wouter Bracke. https://difusion.ulb.ac.be/vufind/Record/ULB-DIPOT:oai:dipot.ulb.ac.be:2013/366721/Details